Ceremonial Entries, Municipal Liberties and the Negotiation of Power in Valois France, 1328-1589 - Murphy, Neil (Rulers & Elites, 2016)
Neil Murphy considers the role the French ceremonial entry played in the negotiation between urban elites and the Valois monarchy for rights and liberties. Drawing on extensive research, he shows that ceremonial entries lay at the heart of how the state functioned in later medieval and Renaissance France. Readership: All those interested in the history of later medieval and Renaissance France, as well as those interested in the pre-modern.